Diabetische Pneumopathie = Diabetic pneumopathy - Kopf, Stefan (Diabetologie und Stoffwechsel, 2019)
Breathlessness or dyspnea is a frequent symptom in patients with diabetes and the first disease which has to be excluded is the coronary heart disease. However, previous epidemiological studies have shown that patients with diabetes mellitus have an increased risk for fibrotic pulmonary diseases, such as the idiopathic pulmonary fibrosis (IPF). Recent studies were able to show that patients with newly diagnosed type 2 diabetes have impaired pulmonary oxygen consumption and over 26 % of patients with long-term type 2 diabetes showed restrictive lung function with fibrotic interstitial lung diseases. Especially patients with type 2 diabetes and nephropathy had an 8-fold higher risk for lung diseases. This is not surprising since the pathomechanisms of pulmonary fibrosis and diabetic complications have much in common: reactive oxygen species induce DNA-damage with consecutive activation of inflammatory cytokines which induce fibrotic remodeling of the tissue. This leads us to the suggestion that patients with diabetes, albuminuria and breathlessness should be examined for interstitial lung disease on regular basis. However, data regarding the natural course of diabetic pneumopathy and therapeutic approaches are still missing. Small intervention studies with IPF-patients could show that sports and physical activity were able to stabilize the disease progression.